Congitive-onomasiological aspect of english cardiovascular terminology - Bespala, Liliia; Turpak, Mariia; Беспала, Лілія Володимирівна (Publishing House of Polonia University «Educator», 2019)
The present work deals with the cognitive-onomasiological aspect of English cardiological terminology. The purpose of the study is to determine the general principles of conceptualizing information about human circulatory system in the English language worldview.
Keywords: cognitive linguistics; concept; frame; onomasiological models